Midlife occupational cognitive requirements protect cognitive function in old age by increasing cognitive reserve - Kleineidam, Luca; Wolfsgruber, Steffen; Weyrauch, Anne-Sophie; Zulka, Linn E.; Forstmeier, Simon; Roeske, Sandra; van den Bussche, Hendrik; Kaduszkiewicz, Hanna; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Fuchs, Angela; et al. (Frontiers in Psychology, 2022)
Several lifestyle factors promote protection against Alzheimer’s disease (AD) throughout a person’s lifespan. Although such protective effects have been described for occupational cognitive requirements (OCR) in midlife, it is currently unknown whether they are conveyed by brain maintenance (BM), brain reserve (BR), or cognitive reserve (CR) or a combination of them. Therefore, we systematically derived hypotheses for these resilience concepts and tested them in the population-based AgeCoDe cohort and memory clinic-based AD high-risk DELCODE study. The OCR score (OCRS) was measured using job activities based on the O*NET occupational classification system. Four sets of analyses were conducted: (1) the interaction of OCR and APOE-ε4 with regard to cognitive decline (N=2,369, AgeCoDe); (2) association with differentially shaped retrospective trajectories before the onset of dementia of the Alzheimer’s type (DAT; N=474, AgeCoDe); (3) cross-sectional interaction of the OCR and cerebrospinal fluid (CSF) AD biomarkers and brain structural measures regarding memory function (N=873, DELCODE); and (4) cross-sectional and longitudinal association of OCR with CSF AD biomarkers and brain structural measures (N=873, DELCODE). Regarding (1), higher OCRS was associated with a reduced association of APOE-ε4 with cognitive decline (mean follow-up=6.03 years) , consistent with CR and BR. Regarding (2), high OCRS was associated with a later onset but subsequently stronger cognitive decline in individuals converting to DAT, consistent with CR. Regarding (3), higher OCRS was associated with a weaker association of the CSF Aβ42/40 ratio and hippocampal volume with memory function, consistent with CR. Regarding (4), OCR was not associated with the levels or changes in CSF AD biomarkers (mean follow-up=2.61 years) . We found a cross-sectional, age-independent association of OCRS with some MRI markers, but no association with 1-year-change. OCR was not associated with the intracranial volume. These results are not completely consistent with those of BR or BM. Our results clearly support the link between OCR and CR. Promoting and seeking complex and stimulating work conditions in midlife could therefore contribute to increased resistance to pathologies in old age and might complement prevention measures aimed at reducing pathology.